Does shoe heel design influence ground reaction forces and knee moments during maximum lunges in elite and intermediate badminton players? - Lam, W.-K.; Ryue, J.; Lee, K.-K.; Park, S.-K.; Cheung, J. T.-M.; Ryu, J. (PLOS ONE, 2017)
Background: Lunge is one frequently executed movement in badminton and involves a unique sagittal footstrike angle of more than 40 degrees at initial ground contact compared with other manoeuvres. This study examined if the shoe heel curvature design of a badminton shoe would influence shoe-ground kinematics, ground reaction forces, and knee moments during lunge. Methods: Eleven elite and fifteen intermediate players performed five left-forward maximum lunge trials with Rounded Heel Shoe (RHS), Flattened Heel Shoe (FHS), and Standard Heel Shoes (SHS). Shoe-ground kinematics, ground reaction forces, and knee moments were measured by using synchronized force platform and motion analysis system. A 2 (Group) x 3 (Shoe) ANOVA with repeated measures was performed to determine the effects of different shoes and different playing levels, as well as the interaction of two factors on all variables. Results: Shoe effect indicated that players demonstrated lower maximum vertical loading rate in RHS than the other two shoes (P < 0.05). Group effect revealed that elite players exhibited larger footstrike angle, faster approaching speed, lower peak horizontal force and horizontal loading rates but higher vertical loading rates and larger peak knee flexion and extension moments (P < 0.05). Analysis of Interactions of Group x Shoe for maximum and mean vertical loading rates (P < 0.05) indicated that elite players exhibited lower left maximum and mean vertical loading rates in RHS compared to FHS (P < 0.01), while the intermediate group did not show any Shoe effect on vertical loading rates. Conclusions: These findings indicate that shoe heel curvature would play some role in altering ground reaction force impact during badminton lunge. The differences in impact loads and knee moments between elite and intermediate players may be useful in optimizing footwear design and training strategy to minimize the potential risks for impact related injuries in badminton.